2009
DOI: 10.1007/s10551-010-0602-2
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Networking: An Ethical Approach

Abstract: cronyism, network misconduct, network ethics, virtue ethics, practice of networking, social networks,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 89 publications
0
17
0
1
Order By: Relevance
“…A set of rules should be predefined as to how such issues are handled. i) Externally controlled transparency-related regulations are more effective than that are implemented by an agency itself (Lindstedt and Naurin, 2010).…”
Section: Lack Of Transparency and Accountabilitymentioning
confidence: 99%
“…A set of rules should be predefined as to how such issues are handled. i) Externally controlled transparency-related regulations are more effective than that are implemented by an agency itself (Lindstedt and Naurin, 2010).…”
Section: Lack Of Transparency and Accountabilitymentioning
confidence: 99%
“…Scholars have acknowledged the importance of decision makers' perceptions in deciding to engage in particular actions. For instance, individuals' perception of uncertainty within their environment will have an impact on internal and external networking activities (Sawyerr 1993) which may include ethically questionable practices such as gratuity and bribery (Mele 2009). Similarly, managers' perceptions of financial constraints and of competition intensity in a market influence firms' decision to bribe (Martin et al 2007).…”
Section: Ethical Issues: Objective or Constructedmentioning
confidence: 99%
“…We have demonstrated that cronyism will have negative consequences for individuals and organizations. In particular, cronyism damages employee trust and perceptions of justice (Melé ). Furthermore, management is viewed as less trustworthy by employees when HR decisions are based on guanxi (Chen, Chen and Xin ).…”
Section: Discussionmentioning
confidence: 99%
“…Khatri and Tsang () assert that cronyism negatively affects job satisfaction, organizational commitment, organizational performance, and overall morale, but positively affects the negative behaviors of ingratiation and organizational inertia. Several scholars argue that cronyism is contrary to distributive justice, which applies objective criteria in allocating rewards, thus promoting equality and avoiding favoritism (Khatri and Tsang ; Melé ; Pelletier and Bligh ). Through a survey of 76 employees in a southern California government agency, Pelletier and Bligh () found that employees’ perceptions of cronyism were articulated as top leaders giving preferential treatment to ingroup members.…”
Section: Cronyism In Relational Collectivist Culturesmentioning
confidence: 99%